2022
DOI: 10.2196/31381
|View full text |Cite
|
Sign up to set email alerts
|

Educators' Perspectives on Integrating Technology Into Sexual Health Education: Implementation Study

Abstract: Background In the last decade, the use of technology-based sexual health education has increased. Multiple studies have shown the feasibility of technology-based interventions, while a subset has also shown efficacy in improving youths’ sexual health outcomes such as increased condom use and knowledge. However, little is known about health educators’ experiences in integrating technology to augment sexual health curricula. Objective The purpose of this … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 33 publications
0
0
0
Order By: Relevance
“…The study conducted by J Decker, et al, [52] demonstrates technology issues affecting SRH technology implementation processes, aiming to improve adolescent health, such as increasing condom usage and knowledge. Health educators are mostly also non-technology, nor SRH conform, to educated youth due to the lack of information provided.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study conducted by J Decker, et al, [52] demonstrates technology issues affecting SRH technology implementation processes, aiming to improve adolescent health, such as increasing condom usage and knowledge. Health educators are mostly also non-technology, nor SRH conform, to educated youth due to the lack of information provided.…”
Section: Discussionmentioning
confidence: 99%
“…School and health educators also play a significant role in the implementation and usage of such tools, as they provide positive feedback on their usage in communities. The study by Decker et al [ 46 ] demonstrated technology issues affecting the implementation of SRH technologies aimed at improving adolescent health, such as increasing condom usage and knowledge. Health educators are often not well-versed in technology or SRH education, leading to challenges in educating youth due to insufficient information provided.…”
Section: Discussionmentioning
confidence: 99%